Examining the case for functional behavior assessment as an evidence-based practice for students with emotional and behavioral disorders in general education classrooms. Issue 1 (2nd January 2017) - Scott, Terrance M.; Alter, Peter J.
ABSTRACT: This article is a review of functional behavior assessment studies in general education setting for students with emotional and behavioral disorders. The studies were assessed in accordance with published standards for evidence-based practices. Overall, few studies met criteria for inclusion in this review and even fewer studies included all three parts of a complete FBA. Results indicate that there are few studies of FBA that specifically address students with behavior problems in general education. Although FBA may have future promise for the described setting and population, there currently is too little information available and lack of consistency in practice to yet claim it is an evidence-based practice.